Actions characterization of students and teacher who explore learning objects in Mathematic classes (Research, Society and Development, 2021)
In this article we present the results of a research that sought to characterize the actions of students and teacher in Mathematic classes in which the subjects investigated explored a learning object. The datas, collected through field notes and video recordings, were obtained during the course of three mathematic classes with students from the Final Years of Elementary School. Content Analysis was used as a method of data collection and analysis, and through its procedures were obtained: 20 categories and 54 subcategories of teaching actions; and 30 categories and 91 subcategories of students actions. When comparing the categories we found with those that emerged from investigations resulting from lecture classes and classes based on manipulative didatic materials, we realized that classes based on the use of learning objects produced a greater number of categories of teacher and students actions; we also identified the existence of some similar categories in these different types of classes.